2001
DOI: 10.1046/j.1365-2141.2001.03156.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of low serum vitamin B12 in a multi‐ethnic Israeli population

Abstract: This study ascertained serum vitamin B12 levels among patients with Gaucher disease and among healthy Israelis. Serum B12 and metabolites' levels were studied in consecutive adult patients with Gaucher disease not treated with enzyme plus Ashkenazi Jewish neighbour‐controls, together with healthy blood‐donor volunteers of various ethnicities. Each group showed a high incidence of low serum B12 concentrations, with a 22·3% incidence among Ashkenazi Jews and 40% among patients with Gaucher disease. These finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 10 publications
3
32
1
Order By: Relevance
“…This is similar to a previous report from north Jordan on 216 healthy individuals by Fora and Mohammad where a suboptimal (< 222 pg/mL) serum level of B 12 was observed in 48.1% of patients [14], and also similar to reports from Israel by Masalha et al (49%) and Gielchinsky et al (31%) [15,16]. Similar reports of high prevalence in this region came from Turkey (46.8%) [17] and the Islamic Republic of Iran (26.7%) [18].…”
Section: Discussionsupporting
confidence: 81%
“…This is similar to a previous report from north Jordan on 216 healthy individuals by Fora and Mohammad where a suboptimal (< 222 pg/mL) serum level of B 12 was observed in 48.1% of patients [14], and also similar to reports from Israel by Masalha et al (49%) and Gielchinsky et al (31%) [15,16]. Similar reports of high prevalence in this region came from Turkey (46.8%) [17] and the Islamic Republic of Iran (26.7%) [18].…”
Section: Discussionsupporting
confidence: 81%
“…The findings from several studies performed in different clinical settings have confirmed that serum vitamin B12 is a relatively poor marker with low sensitivity and specificity in predicting vitamin B12 status and that holoTC is a useful diagnostic indicator for this purpose [3,5]. In addition, a few studies performed in different countries and ethnic groups have shown differences in the prevalence of vitamin B12 deficiency and have also revealed that holoTC is a more sensitive marker than total serum vitamin B12 for investigating vitamin B12 status [5,12,[16][17][18][19]. However, most of the previous studies were performed using radioimmunoassays, and very few studies have been performed with the more recent microparticle enzyme immunoassays.…”
mentioning
confidence: 99%
“…In Gaucher disease, ferritin levels are generally elevated without other biochemical evidence of iron overload, consistent with anemia of chronic disease, whereas typical iron deficiency anemia is characterized by low serum iron, low transferrin saturation and low ferritin levels [9]. In a study among Ashkenazi Jews, it was reported that vitamin B12 levels tended to be lower in the diseased population and decreased in the course of ERT [10]. We gave the patient parenteral vitamin B12 supplementation due to the low level.…”
Section: Discussionmentioning
confidence: 99%